Synaptopathology Involved in Autism Spectrum Disorder - Guang, Shiqi; Pang, Nan; Deng, Xiaolu; Yang, Lifen; He, Fang; Wu, Liwen; Chen, Chen; Yin, Fei; Peng, Jing (Frontiers in Cellular Neuroscience, 2018)
Autism spectrum disorder (ASD) is a group of multifactorial neurodevelopmental disorders characterized by impaired social communication, social interaction and repetitive behaviors. ASD affected 1 in 59 children, about 4 times more common among boys than among girls. There is a strong genetic component to ASD susceptibility, in conjunction with developmental early environmental factors, together contribute to the pathogenesis of ASD. Multiple studies have unveiled that mutations in genes like NRXN, NLGN, SHANK, TSC1/2, FMR1 and MECP2 converge on the common cellular pathways that intersect at synapses. These gene products encompass cell adhesion molecules, scaffolding proteins, regulators of transcription and protein levels, affecting synapses in various aspects including synapse formation and elimination, synaptic transmission and plasticity, which suggests pathogenesis of ASD, at least in part, be attributed to synaptic dysfunction. In this review article, we focus on major genes and signaling pathways implicated in synaptic abnormalities underlying ASD and discuss the molecular, cellular and functional studies of ASD animal models.